Heeding the call from the promised land: identity work of self-initiated expatriates before leaving home. Issue 20 (13th November 2022) - Moulaï, Kamila; Manning, Stephan; Guttormsen, David S. A.
Abstract: Despite growing interest in self-initiated expatriates (SIEs), we know little about how SIEs develop the aspiration to leave both home employers and home countries behind. Based on rich empirical data from Western European SIEs, who migrated to North America, we explored key dynamics of identity work leading up to their decision to expatriate. We found that an SIE's self-concept as a talented professional is initially negatively impacted by interactions with their home employers. However, through elevating conversations with 'trusted outsiders', SIEs engage in re-crafting a more positive sense of self. SIEs associate the trusted outsiders' foreign professional background with idealized future work environments, the 'promised land', in which they see their elevated selves fulfilled. Our findings have important implications for research on drivers of self-initiated expatriation, voluntary turnover and talent management.